Surface velocity estimation of uids using millimetre-wave radar - Erhart, Christian; Lutz, Steffen; Köhler, Johannes; Mantz, Hubert; Walter, Thomas; Weigel, Robert (European Microwave Conference (EuMC), 2015)
This paper presents a microwave sensor which allows to measure the surface velocity of uids via determining the Doppler shift of the scattered signal. The design of the sensor follows a modular system. Thus the antenna as well as the ampli er can be exchanged easily. Measurements in industrial as well as in natural environments with di erent antennas will be shown. An extended focus will be on the development of a dielectrical waveguide antenna for near distance measurements in industrial environments. Dependency of the signal strength on the angle of polarisation will be investigated and an approach to estimate the velocity from the measured data will be introduced.
elib2cris::1512001600,erhart2015a